THE EFFECTIVENESS OF USING DUOLINGO INTERACTIVE MEDIA ON THE MASTERY OF GERMAN VOCABULARY - Marshalo R. Kakerissa; Juliaans E. R. Marantika; Kalvin Karuna (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2022)
This study aims to describe the effect of using Duolingo interactive media on increasing German vocabulary. This research was conducted with a sample of 16 elementary level students at the German Language Education Study Program, Pattimura University. The data were collected through pre-test and post-test and supported by a questionnaire as supporting data. The data collected were analyzed using t test analysis techniques, and supporting data were analyzed using descriptive analysis techniques. The results showed that the calculation result of t=4,583 was higher than the value of t-table, and indicated the positive effect of using Duolingo interactive media on German vocabulary mastery. This finding is supported by the results of a questionnaire that describes the advantages of using Duolingo in terms of the intended use, user groups, application features, space and time, cost, and accessibility. Finally, it can be concluded that the use of Duolingo interactive media is effective in increasing the mastery of German vocabulary.